Effect of salidroside on cultured myocardial cells anoxia/reoxygenation injuries - Ye Yu-Chong; Chen Qin-Ming; Jin Kai-Ping; Zhou Sheng-Xiang; Chai Feng-Ling; Hai Ping (Acta Pharmacologica Sinica, 2016)
The effects of salidroside (p-hydroxyphenethyl glucoside, Sal, first isolated and synthesized in China) on reoxygenation damages were studied on cultured myocytes from neonatal rat hearts. At least 80% of cells in the form of monolayer contracted spontaneously on cultured 72 h, then the cells were used in the contractility experiment. After anoxia 3 h and reoxygenation for 1 h the beating of myocardial cells was slowed down and the lactate dehydrogenase (LDH) liberated by myocardial cells was increased. Electron microscopy of myocardial cells revealed localized defects of cell membrane, dilatation of endoplasmic reticulum, and swelling of mitochondria. One h before anoxia, addition of Sal 10 and 30 micrograms.ml-1 increased the beat rate of myocardial cells, depressed the release LDH of from myocytes, and the myocardial ultrastructure was normal during anoxia and reoxygenation. Hence Sal may provide some protective effects on the anoxia/reoxygenation damages upon myocardium.